Dimensional assessment of behavioral changes in the cuprizone short-term exposure model for psychosis. (June 2016) - Kondo, Mari A.; Fukudome, Daisuke; Smith, Dani R.; Gallagher, Michela; Kamiya, Atsushi; Sawa, Akira
Highlights: Cuprizone short-term exposure (CSE) models brain inflammation-associated psychosis. Comprehensive behavior assessment of CSE model is done using a dimensional approach. The CSE model may be useful to further our understanding of psychosis mechanisms. Abstract: Recent clinical studies have suggested a role for immune/inflammatory responses in the pathophysiology of psychosis. However, a mechanistic understanding of this process and its application for drug discovery is underdeveloped. Here we assessed our recently developed cuprizone short-term exposure (CSE) mouse model across behavioral domains targeting neurocognitive and neuroaffective systems. We propose that the CSE model may be useful for understanding the mechanism associating inflammation and psychosis, with applications for drug discovery in that context.